Efeito da própolis sobre a produção de citocinas por camundongos submetidos a estresse crônico e desafiados com melanoma - Missima, Fabiane [UNESP] (2009)
Several studies have shown that stress affects the immune system, promoting the progression of cancer. Since propolis is a honeybee product showing immunomodulatory and antitumoral activities, the goal of this work was to evaluate propolis effect on Th1 (IL-2 and IFN-) and Th2 (IL-4 and IL-10) cytokines’ expression and production by melanoma-bearing mice submitted to immobilization stress. In groups without melanoma, stress did not affect IL-2, IL-4 and IL-10 gene expression. Propolis treatment of stressed animals did not influence these cytokines expression as well. On the other hand, IL-2 and IL-10 expression was inhibited in melanoma-bearing mice, stressed or not. Th1 cytokines production was also inhibited in melanoma-bearing mice. Propolis administration to melanoma-bearing mice submitted to stress stimulated IL-2 expression, as well as Th1 (IL-2 and IFN-) production, indicating the activation of antitumor cell-mediated immunity. Propolis also stimulated IL-10 expression and production, what may be related to immunoregulatory effects. Our data indicate that propolis showed an immunomodulatory activity in this assay, what may be related to its antitumoral action in vivo. Further investigation will help to understand propolis usefulness during stress.